The structure, phase and chemical composition of CZTSe thin films - Opanasyuk, A.S.; Koval, P.V.; Nam, D.; Cheong, H.; Jeong, A.R.; Jo, W.; Ponomarev, A.G. (Functional Materials, 2014)
Cu₂ZnSnSe₄ thin films obtained by co-evaporation of components using an electron beam evaporation system were investigated by scanning electron microscopy, X-ray analysis, PIXI and RBS methods. The analysis of the diffraction patterns showed that the films are almost single-phased and contain mainly CZTSe compound, which has a tetragonal kesterite lattice type. The samples have textural growth of [211]. The lattice parameters of the material varied in the range of a = (0.56640-0.56867) nm, c = (1.13466-1.13776) nm, c/2a = 0.9983-1.0017 which correlate well with the reference data in a stable phase CZTSe compounds. From our PIXE analyses we assessed the influence of the growth conditions on the samples chemical composition and mapped the surface distribution.